(untitled) (Ius Novum, 2024)
The considerations undertaken in this article concern the structure of the concession procedure conducted for audiovisual concessions. If by structure we understand the relationship between the elements constituting a given type of proceeding, then the concession procedure before the KRRiT is unique, as the decision on the concession is entrusted to two bodies within a single administrative proceeding. Against this backdrop, numerous procedural doubts arise regarding the place and role of the KRRiT and the President of the KRRiT in such proceedings, as both bodies decide on radio and television concessions. The joint action of these bodies in issuing a decision is an original solution in Polish law, which warrants theoretical justification. The article proposes a solution based on the exercise of joint competence by these authorities. Such a construction is permissible and appears to result from existing regulations under the Law on Radio and Television Broadcasting; however, it fundamentally changes the structure of the entire procedure, necessitating a fresh examination of procedural relations, the responsibilities of the authorities, and the mechanisms for controlling their actions. The solution presented in this article, beginning with the concept of the structure of concession proceedings, aims to ensure the efficiency of these proceedings while primarily safeguarding the rights of the entities involved.